THE EFFECT OF PRODUCT QUALITY, CUSTOMER TESTIMONIALS AND PRICE PERCEPTION ON THE PURCHASE INTENTION OF GENERATION Z CONSUMERS ON MS GLOW PRODUCTS IN LHOKSEUMAWE CITY - Adnan; Suryani; Munandar; M.Subhan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to determine the effect of product quality on consumer purchase intention, customer testimonials on consumer purchase intention and price perception on consumer purchase intention, also simultaneously as the influence of product quality, customer testimonials and price perception on consumer purchase intention Generation Z on MS Glow products in lhokseumawe city. This research method uses quantitative method with model selection using multiple linear regression, this research uses primary and secondary data where data collection is online and offline, by distributing links through google form and distributing questionnaires to respondents in lhokseumawe city, with non probability sampling techniques with criteria: consumers aged <17 years to 27 year, consumers who intend and who have never used MS Glow products, with a sample of 100 respondents, this study also used a likert scale. The results of this study prove that product quality has a positive and significant effect on consumer purchase intention, customer testimonials have a positive and significant effect on consumer purchase, and price perception has a positive and significant effect on consumer purchase intention. Furthermore, the implications of this study are divided into two, namely: theoretical implications and managerial implications, where theoretical implications are the results that distinguish previous research from current research, with the aim to add insight and understanding for researchers and strengthen strengthen research results, while managerial implications refer to recommendations for decision making or the findings of researchers can provide information and useful advice for managers in making decisions, both individually and organizationally.